TINGKAT KEPUASAN APOTEK DI WILAYAH LUMAJANG TERHADAP DISTRIBUSI OBAT OLEH PEDAGANG BESAR FARMASI - Kukuh Judy Handojo,Pradanu Satria Rakhmanta,Diyan Ajeng R (AKADEMI FARMASI JEMBER, 2017)
PBF services in Lumajang region need to improve the quality of service, includingdelivery time often exceeds the time that had been promised, complaints regarding medication errors and difficulty getting accountability, the price has changed in a short time, and the service was not constant. The purpose of this study was to determine the level of drug store Lumajang region against drug distribution by PBF in tangible dimension (direct evidence), reliablity (reliability), responsivines (responsiveness),assurance (assurance), empathy (caring). Samples were selected in this research is all drug store in Lumajang totaling 30 pharmacies. The research design in this study is descriptive by using survey method.Based on the data collection process,there were only 30 drug store that are willing to be respondenden has qualified for data processing and it can be concluded that the level of satisfaction Pharmacy Lumajang region on tangible dimension (direct evidence) of 86.24%, expressed satisfaction,reliability dimension (reliability) by 80%, otherwise satisfactory, dimensions responsiviness (responsiveness) of 75.84%, expressed quite satisfactory, dimensions assurance (guarantee) amounting to 86.11%, declared satisfactory, the dimensions of empathy (caring) amounted to 86.94%, otherwise satisfactory. Based on the above data,it needs to be evaluated in five dimensions, from the evaluation it would appear that satisfaction level of drug store in Lumajang to PBF service (drug distribution)reach 83,02% and including the satisfactory category .Keywords: Level of satisfaction - Drugs distribution – PBF